2005
DOI: 10.1111/j.1468-005x.2005.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Teleworking practice in small and medium-sized firms: management style and worker autonomy

Abstract: In an empirical study of teleworking practices amongst small and medium-sized enterprises (SMEs) in West London, organisational factors such as management attitudes, worker autonomy and employment flexibility were found to be more critical than technological provision in facilitating successful implementation. Consequently, we argue that telework in most SMEs appears as a marginal activity performed mainly by managers and specialist mobile workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 20 publications
(25 reference statements)
3
61
0
5
Order By: Relevance
“…According to the chairperson of AMSP, Karel Havlicek, the current business requires the following essential prerequisites for success: women's artfulness, resilience, the ability to concentrate on the result and not on the victory, and having a clear mind to focus on work. Besides, being self-employed enables to take advantage of telework (Clear & Dickson, 2005). It can be attractive especially for women who want to fulfil their multiple role of wife, mother, employee, housewife and others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the chairperson of AMSP, Karel Havlicek, the current business requires the following essential prerequisites for success: women's artfulness, resilience, the ability to concentrate on the result and not on the victory, and having a clear mind to focus on work. Besides, being self-employed enables to take advantage of telework (Clear & Dickson, 2005). It can be attractive especially for women who want to fulfil their multiple role of wife, mother, employee, housewife and others.…”
Section: Resultsmentioning
confidence: 99%
“…A business size at start-up is an important variable included in a number of empirical studies (Cowling et al, 2015). According to Clear and Dickson (2005), there are some task elements that must be taken into account when considering the autonomy: the method of working, pace of work, procedures, scheduling, work criteria, work goals, workplace, work evaluation, working hours, kind of work and amount of work. The authors state that differing levels of employees´ autonomy are reflected in the level of trust of employers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Similarly, Haddon and Brynin (2005) show that managers and professionals predominate among European teleworkers. It is thought that professionals, managers, and/or knowledge workers tend to have autonomy and control over their work and work environment, and thus are relatively likely to opt to telework (Clear and Dickson, 2005;Taskin and Edwards 2007;Tremblay and Najem, 2010). By extension, we presume that more educated workers would tend to have positive telework experiences, while lower-wage workers would tend to have the opposite experience.…”
Section: Independent and Control Variablesmentioning
confidence: 99%
“…Finally, according to Clear and Dickson (2005), teleworking exists in firms of any size or industry sector, although Mayo et al (2009) found that teleworking was more prevalent in smaller organizations. We expect that telework will be more prevalent in the service sector, since many studies (e.g.…”
Section: Independent and Control Variablesmentioning
confidence: 99%
“…Some management studies in SMEs have pointed out the role of social relations in influencing day-to-day work practices (Clear and Dickson, 2005;Dundon and Wilkinson, 2003). Similar to the contact-centre literature, this strand of research is predominantly Anglo-Saxon driven and has largely exemplified the patriarchal and autocratic SME (Holiday, 1995;Rainnie, 1989;Saini and Budhwar, 2008).…”
Section: Introductionmentioning
confidence: 99%